A new HLA allele, HLA‐B*08:122, described in an unrelated donor of Caucasian origin. Issue 6 (22nd October 2014) - Buffi, O.; Iannelli, S.; Iliescu, A.; Bontadini, A.; Nesci, S.
<x xml:space="preserve">Abstract</x> A new human leukocyte antigen‐B allele was found in an unrelated Italian donor.